Організація самостійної роботи з педагогічних дисциплін у ВНЗ технічного профілю = Organization of independent work of pedagogical disciplines in Universities technical profile - Sokal, Valentine (Journal of Education, Health and Sport, 2016)
Sokal Valentine. Організація самостійної роботи з педагогічних дисциплін у ВНЗ технічного профілю = Organization of independent work of pedagogical disciplines in Universities technical profile. Journal of Education, Health and Sport. 2016;6(12):642-654. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221122 http://ojs.ukw.edu.pl/index.php/johs/article/view/4108 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016. ОРГАНІЗАЦІЯ САМОСТІЙНОЇ РОБОТИ З ПЕДАГОГІЧНИХ ДИСЦИПЛІН У ВНЗ ТЕХНІЧНОГО ПРОФІЛЮ Сокаль Валентина Національний університет водного господарства та природокористування, м. Рівне, Україна Organization of independent work of pedagogical disciplines in universities technical profile Sokal Valentine National University of water management and nature resources use, Rivne, Ukraine Анотація. В статті розглядаються особливості організації самостійної роботи з педагогічних дисциплін у вищому навчальному закладі технічного профілю. Обґрунтовані групи мотивів, що спонукають студентів займатися самостійною роботою. Визначені умови ефективної організації самостійної роботи, як складової формування професійних компетентностей студентів вищих навчальних закладів. Ключові слова. Самостійна робота, самоосвіта, мотиви навчання, професійні інтереси, творчі завдання. Аннотация. В статье рассматриваются особенности организации самостоятельной работы по педагогическим дисциплинам в высшем учебном заведении технического профиля. Обоснованы группы мотивов, побуждающих студентов заниматься самостоятельной работой. Определены условия эффективной организации самостоятельной работы, как составляющей формирования профессиональных компетенций студентов высших учебных заведений. В основу организации самостоятельной работы по педагогическим дисциплинам возложены эмоционально-психологические и интеллектуальные мотивы, позволяющие выбрать задание, которое приносит эмоциональное удовлетворение, способствует творческому развитию личности студента и побуждает к научным исследованиям. Сформированы навыки самостоятельной работы, впоследствии, после окончания вуза, помогут молодому специалисту выполнять свои профессиональные функции и приобретать новые знания. При организации самостоятельной работы по педагогическим дисциплинам в техническом ВУЗе преимущественно используется индивидуальная внеаудиторная работа: конспектирования, цитирование, подготовка научных тезисов, статей, рефератов, презентаций, викторин; подготовка вопросов для педагогических исследований (интервью, беседы, анкетирование); подготовка учебно методического комплекса дисциплины; подготовка к проведению лекционного, практического и лабораторного занятия. Важное значение имеет организация систематического контроля за результатами самостоятельной работы студентов со стороны преподавателя. Ключевые слова. Самостоятельная работа, самообразование, учебные мотивы, профессиональные интересы, творческие задания. Summary. The article describes peculiarities of the individual work organization in pedagogical disciplines taught in the higher technical education institutions. The groups of reasons which motivate students to be involved in the individual projects are clearly justified. This research helped to define the conditions of the effective individual work organization which in its turn is an integral part of the students' professional competencies formation. Key words. Individual work, self-education, reasons-to-learn, professional interests, creative tasks.